Functional fantasies: the regulatory role of grandiose fantasizing in pathological narcissism - Finch, Ellen F.; Hooley, Jill M. (Frontiers in Psychiatry, 2023)
Introduction Pathological narcissism is characterized by maladaptive efforts to maintain a bolstered but fragile sense of self. Clinical theory suggests that grandiose fantasizing may be one form of this self-regulation. However, no empirical research has directly assessed the regulatory function of grandiose fantasizing in narcissism. Here, we examine (1) whether people scoring higher in narcissism choose to engage in grandiose fantasizing to regulate themselves when they are feeling down and (2) whether grandiose fantasizing is a more efficacious self-esteem and affect regulator for people scoring higher in narcissism than it is for those scoring lower in narcissism. Methods Adult participants (N = 189) completed a self-report measure of narcissism and were randomized to either a negative mood induction or filler task condition. Then, participants wrote about a future event to make themselves feel better, choosing between a positive affect word or a grandiose word to guide their writing. Throughout the study, participants reported their state positive and negative affect and self-esteem. A secondary sample (N = 128) of adult participants rated the future event writing of the original participants. Results Supporting the validity of the study design, grandiose future events significantly differed from positive future events (e.g., they were rated by independent raters as less plausible, more ambitious, more active, and occurring further in the future). Participants scoring higher in narcissism and participants who experienced larger increases in negative affect were more likely to choose to engage in grandiose fantasizing. Grandiose fantasizing was more effective at decreasing negative affect among participants scoring higher in narcissism than those scoring lower in narcissism, whereas positive future thinking was equally effective at decreasing negative affect across levels of narcissism. Discussion This study demonstrates that people scoring higher in narcissism are more likely to choose to engage in grandiose fantasizing to make themselves feel better. It further demonstrates that grandiose fantasizing is a more efficacious affect regulator for those scoring higher in narcissism.